2005
DOI: 10.1177/000331970505600108
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Antibody Titers Are Reduced by Statin Therapy in Dyslipidemic Subjects: A Pilot Study

Abstract: Antibody titers to heat shock protein (Hsp)-60 and -65 are positively related to risk of vascular disease and cardiovascular endpoints. There are few data on the factors that regulate the levels of these antibodies. It is known that the statins have antiinflammatory and immunoregulatory properties. The authors examined the effects of 2 statins, simvastatin (Zocor) and atorvastatin (Lipitor) on antibody titers to Hsp-60, -65, and -70 in a group of dyslipidemic patients. Twenty patients attending a lipid clinic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We also found that there was an association between anti-HSP60 antibody titers and anti-HSP70 antibody titers, although the association was weak. This finding supports the recent results from Ghayour-Mobarhan, et al, 15) but is in conflict with the results reported by Kocsis, et al who found that there was no association between the titers of HSP70 antibody and either the anti-HSP60 or anti-HSP65 titer. 29) It is interesting to learn that there was no relation between antibody titers to HSPs and other inflammatory factors, ie, hsCRP and IL-6 (data not shown).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We also found that there was an association between anti-HSP60 antibody titers and anti-HSP70 antibody titers, although the association was weak. This finding supports the recent results from Ghayour-Mobarhan, et al, 15) but is in conflict with the results reported by Kocsis, et al who found that there was no association between the titers of HSP70 antibody and either the anti-HSP60 or anti-HSP65 titer. 29) It is interesting to learn that there was no relation between antibody titers to HSPs and other inflammatory factors, ie, hsCRP and IL-6 (data not shown).…”
Section: Discussionsupporting
confidence: 62%
“…Our results conflicted with those of Ghayour-Mobarhan and colleagues who reported that statin treatment was associated with a reduction in antibody titers to HSP60, HSP65, and HSP70. 15) We believe that this discrepancy may be explained by the underlying differences in the nature of the subjects. The subjects in this study were patients who had undergone revascularization (PCI) and were previously treated with lipid-lowering medication during the acute-phase (7-10 days).…”
Section: Discussionmentioning
confidence: 96%
“…It is known that the statins have antiinflammatory, antioxidant, and immunoregulatory properties (26,27 ). GhayourMobarhan et al (28 ) first reported that statin treatment was associated with a significant reduction in median antibody concentrations to Hsp60, Hsp65, and Hsp70 in dyslipidemic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…More and more attention is being paid to the role of the immune system in the pathogenesis of atherosclerosis because CD4 + T-cells and macrophages were found to be involved in its development. HSPs released from damaged cells during inflammatory response are particularly important autoantigens, which are assigned to the development of atherosclerotic plaques [60, 61]. In an animal model, the presence of specific HSP60 was demonstrated in the spleen and lymph nodes in both B and T lymphocytes, which was suggested to confirm autoimmune stimulation by HSP60 and indicate the role of HSP60 as a stimulator of the immune system in the development of atherosclerosis [6265].…”
Section: Hsps In Autoimmune Diseasesmentioning
confidence: 99%